ADM energy and infra-gravitons - A.P. Balachandran; Babar Qureshi (Physics Letters B, 2017)
In QED and QCD [1,2], infrared photons and gluons alter the Hilbert space of the theory so that the in and out states live in a Hilbert space carrying a representation of basic commutation relations which is non-equivalent to the standard Fock representation, leading to spontaneous breakdown of Lorentz symmetry and physical effects. These results are generalized here to quantum gravity regarded as an SL(2,C) gauge theory and the shift of the ADM energy density and mass from infrared spin connection (the spin cloud) is discussed.